Cracking the RNA polymerase II CTD code. - Egloff, S; Murphy, S (2008)
The carboxyl-terminal domain (CTD) of the largest subunit of RNA polymerase II comprises multiple tandem conserved heptapeptide repeats, unique to this eukaryotic RNA polymerase. This unusual structure provides a docking platform for factors involved in various co-transcriptional events. Recruitment of the appropriate factors at different stages of the transcription cycle is achieved through changing patterns of post-translational modification of the CTD repeats, which create a readable 'code'. A new phosphorylation mark both expands the CTD code and provides the first example of a CTD signal read in a gene type-specific manner. How and when is the code written and read? How does it contribute to transcription and coordinate RNA processing?